2015
DOI: 10.1007/s00234-015-1583-8
|View full text |Cite
|
Sign up to set email alerts
|

Protected stent retriever thrombectomy prevents iatrogenic emboli in new vascular territories

Abstract: Introduction Diagnostic tools to show emboli reliably and protection techniques against embolization when employing stent retrievers are necessary to improve endovascular stroke therapy. The aim of the present study was to investigate iatrogenic emboli using susceptibility-weighted imaging (SWI) in an open series of patients who had been treated with stent retriever thrombectomy using emboli protection techniques. Methods Patients with anterior circulation stroke examined with MRI before and after stent retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
0
33
2
Order By: Relevance
“…25 Nonetheless, controversies about the relevance of the technique have arisen as in case of aspiration component failure, it might induce a potential delay in reperfusion which could have been avoided using the SR technique and also because this technique does not use a proximal flow arrest with Balloon guide catheter known to prevent embolus in new territory. 26,27 Although no comparative studies have been conducted with ADAPT versus the validated SR technique, some evidences suggest noninferiority 9 or superiority of the ADAPT technique to achieve better reperfusion rates. 7 In this perspective, more insights are needed to identify which patients may benefit from this technique.…”
Section: Discussionmentioning
confidence: 99%
“…25 Nonetheless, controversies about the relevance of the technique have arisen as in case of aspiration component failure, it might induce a potential delay in reperfusion which could have been avoided using the SR technique and also because this technique does not use a proximal flow arrest with Balloon guide catheter known to prevent embolus in new territory. 26,27 Although no comparative studies have been conducted with ADAPT versus the validated SR technique, some evidences suggest noninferiority 9 or superiority of the ADAPT technique to achieve better reperfusion rates. 7 In this perspective, more insights are needed to identify which patients may benefit from this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular treatment strategies that consequently strive to achieve TICI 3 may be warranted and cost-effective, and their risk:benefit ratios should be evaluated in pertinent studies. The majority of observable distal branch occlusions after MTE—which make the difference between TICI 2b and TICI 3—arise owing to distal embolization during the endovascular procedure 21 24. The rate of TICI 3 recanalizations can therefore be viewed as a suitable and—as shown here—clinically relevant safety measure for studies evaluating MTE devices and techniques.…”
Section: Resultsmentioning
confidence: 82%
“…Reported clinical rates range from 0 to 12.5% embolization to new territory (Table 1). Assessment of distal embolization with angiography can be difficult, and a recent study using susceptibility-weighted imaging indicated that rates may be in the range of 23% [28]. Susceptibility-weighted imaging seems to be more sensitive to detect emboli than digital subtraction angiography.…”
Section: Discussionmentioning
confidence: 99%